Smart Game for Sex Education: Pengembangan Media untuk Meningkatkan Pendidikan Seksual Anak - Tursina, Ade; Veryawan; Vira Adelia (Universitas Lancang Kuning, 2025)
The purpose of the SGSE (Smart Game for Sex Education) media in improving sexual education for children includes the introduction of the boundaries of genitals between men and women, the introduction of body parts that may be touched and may not be touched, and the introduction of normal emotional reactions. The subjects in this study were validators of material experts, media experts, language experts, and 9 children at TAUD Luqmanul Hakim Kindergarten. The results of the material expert validity test obtained a percentage of 92% with the category of